Criminal law - "Herring, Jonathan" (New York, 2011)
This text provides a readable, comprehensive and accessible introduction to Criminal Law. Through the media coverage of high profile trials we all feel that we know something about criminal law, and this text uses such cases to create a real interest and involvement on the part of the student. Features such as 'key words' at the start of each chapter introduce the student to the key topics to be discussed, and 'hot topic' sections analyze the controversial cases of recent years. This new edition has been updated to include discussion on the House of Lords decision on recklessness, and the impact of the Sexual Offences Act.
Keywords: Criminal law